Solvent-dependent on/off valving using selectively permeable barriers in paper microfluidics - Hamidon, N.N.; Salentijn, G.IJ.; Verpoorte, Elisabeth
We report on a new way to control solvent flows in paper microfluidic devices, based on the local pattern- ing of paper with alkyl ketene dimer (AKD) to form barriers with selective permeability for different solvents. Production of the devices is a two-step process. In the first step, AKD-treated paper (hydrophobic) is ex- posed to oxygen plasma for re-hydrophilization. 3D-printed masks are employed to shield certain areas of this paper to preserve well-defined hydrophobic patterns. In the second step, concentrated AKD in hexane is selectively deposited onto already hydrophobic regions of the paper to locally increase the degree of hy- drophobicity. Hydrophilic areas formed in the previous oxygen plasma step are protected from AKD by wetting them with water first to prevent the AKD hexane solution from entering them (hydrophilic exclu- sion). Characterization of the patterns after both steps shows that reproducible patterns are obtained with linear dependence on the dimensions of the 3D-printed masks. This two-step methodology leads to differ- ential hydrophobicity on the paper: (i) hydrophilic regions, (ii) low-load AKD gates, and (iii) high-load AKD walls. The gates are impermeable to water, yet can be penetrated by most alcohol/water mixtures; the walls cannot. This concept for solvent-dependent on/off valving is demonstrated in two applications. In the first example, a device was developed for multi-step chemical reactions. Different compounds can be spotted separately (closed gates). Upon elution with an alcohol/water mixture, the gates become perme- able and the contents are combined. In the second example, volume-defined sampling is introduced. Aqueous sample is allowed to wick into a device and fill a sample chamber. The contents of this sample chamber are eluted perpendicularly with an alcohol/water mixture through a selectively permeable gate. This system was tested with dye solution, and a linear dependence of magnitude of the signal on the sam- ple chamber size was obtained.